Proteomic Studies and Its Application To Biological Samples Using Mass Spectrometry - Güray, Melda Zeynep; Karakaya, Hüseyin Çağlar; Yalçın, Talat (Izmir Institute of Technology, 2017)
Mass spectrometry (MS) is a powerful analytical tool with its application in the field of biological sciences for identification of proteins, defining post-translational modifications, studying protein expression and protein interactions. This thesis presents MS analyses of proteins for defining modifications observed during sample preparation and identification of proteins isolated from clinical samples and microorganisms. The first part of the thesis includes proteomic analysis of antimony resistant L. tropica. The results clearly indicated that the generation of antimony resistance by parasites, either in host organism or in vitro, causes alteration of protein expression levels, and the mechanism of antimony resistance in host organism and in vitro conditions follow different strategies. In the second part of the study, proteomic analysis of Bence Jones proteins isolated from urine of multiple myeloma patients was performed. Gel electrophoresis and MS analysis revealed that the proteins from different patients with different nephrotoxicity have different tendencies to form multimeric structures and contained different type of light chain. In the third part, it was shown that precipitation of proteins in acetone causes +98 u mass artifacts on proteins when analyzed by MS. The parameters affecting the formation of modification was studied and it was revealed that this modification is dependent on solution pH, incubation time and temperature. In the last part, aspartic acid and glutamic acid containing synthetic peptides were shown to be methylated upon incubation in acidified methanol solution. MS analysis revealed that the reaction is dependent on temperature and time and is affected by the type of acid included in methanol solution. All in all, this thesis provides a comprehensive study of proteins by mass spectrometry for identification of proteins from different sources, as well as defining protein modifications observed as artifacts during sample handling in proteomic workflows.

Kütle spektrometrisi (MS), biyolojik bilimler alanında uygulamaları ile protein tanımlanması, post-translasyonel modifikasyonların belirlenmesi, protein ifadelenmesi ve protein etkileşim çalışmaları için güçlü bir analitik yöntemdir. Bu tez, örnek hazırlama sırasında oluşan modifikasyonların belirlenmesi ve klinik örneklerden ve mikroorganizmalardan elde edilen proteinlerin tanımlanması için proteinlerin MS analizlerini sunmaktadır. Çalışmanın ilk bölümü, antimon dirençli L. tropica’nın proteomik analizini içermektedir. Sonuçlar açıkça göstermiştir ki; parazit tarafından konakçı organizmada ya da in vitro koşullarda geliştirilen ilaç dirençliliği, parazitlerde protein ifadelenme düzeylerinde değişikliklere sebep olmuştur ve konakçı hücre ve in vitro koşullarda oluşan ilaç dirençliliği mekanizmaları farklı yollar izlemektedir. Çalışmanın ikinci bölümünde, multipl miyelom hastalarının idrarlarından izole edilen Bence Jones proteinlerinin proteomik analizleri gerçekleştirilmiştir. Jel elektroforezi ve MS analizleri, farklı hastalardan elde edilen farklı nefrotoksik özelliğe sahip proteinlerin, farklı multimer yapılar oluşturduğunu ve farklı tür hafif zincire sahip olduğunu ortaya çıkarmıştr. Üçüncü bölümde, proteinlerin aseton ile çöktürülmesi sırasında asetonun proteinler üzerinde +98 u kalıntılar oluşturduğu MS analizleri ile gösterilmiştir. Bu modifikasyonun oluşumunu etkileyen parametreler çalışılmış ve modifikasyonun çözelti pH’ına, inkübasyon zamanına ve sıcaklığına bağımlı olduğu ortaya çıkarılmıştır. Son olarak, aspartik asit ve glutamik asit içeren sentetik peptitlerin, asidik metanol çözeltisi içinde inkübe edilmesi sebebiyle metillendiği gösterilmiştir. MS analizleri, reaksiyonun sıcaklık ve zamana bağımlı olduğunu ve çözeltinin içeriğinde bulunan asit türünden etkilendiğini ortaya koymuştur. Sonuç olarak; bu tez, proteinlerin farklı kaynaklardan tanımlanması ve aynı zamanda proteomik çalışmalarında örnek hazırlama sırasında oluşan protein modifikasyonlarının belirlenmesinde, proteinlerin MS ile kapsamlı bir şekilde çalışılmasını sağlamaktadır.
Proteomik Çalışmaları ve Kütle Spektrometresi Kullanılarak Biyolojik Örneklere Uygulaması
Thesis (Doctoral)--İzmir Institute of Technology, Chemistry, İzmir, 2017
Full text release delayed at author's request until 2019.06.28
Includes bibliographical references (leaves: 127-141)
Text in English; Abstract: Turkish and English
Keywords: Mass spectrometry; Proteins; Proteomics; Protein modifications; Clinical proteomics